DEVELOPING PEDAGOGICAL CONTENT KNOWLEDGE OF MATHEMATICS PRE-SERVICE TEACHER THROUGH MICROTEACHING LESSON STUDY - Wasilatul Murtafiah; Marheny Lukitasari (Jurnal Pendidikan Matematika, 2019)
This research aimed to describe pedagogical content knowledge of mathematics pre-service teacher through the lesson study application in microteaching. This descriptive qualitative research was conducted in Universitas PGRI Madiun with Mathematics pre-service teachers as subjects. The data were collected through observation, unstructured interviews, and documentation. Data from learning practice and pedagogical content knowledge were analyzed based on a scoring criteria framework that refers to microteaching assessment guidelines. The results showed that there was an increase in mathematics pre-service teacher learning practice (lesson planning increased from average to good, pre-learning activities increased from average to good, while learning activities increased from average to good, and closing activities increased from average to good). There was an increase in mathematics pre-service teacher content knowledge (increased in concept mastery from average to good and increased in material understanding from average to good). There was also an increase in mathematics pre-service teacher pedagogical knowledge (increased in clarity of learning scenarios from average to excellent, increase in the ability to use learning media from average to good, increase in the appropriateness of assessment techniques with learning objectives from average to good).